A Comparative Analysis of Suicide Terrorists and Rampage, Workplace, and School Shooters in the United States From 1990 to 2010. (August 2013) - Lankford, Adam
This study presents results from the first combined quantitative assessment and comparative analysis of suicide terrorists and rampage, workplace, and school shooters who attempt suicide. Findings suggest that in the United States from 1990 to 2010, the differences between these offenders ( N = 81) were largely superficial. Prior to their attacks, they struggled with many of the same personal problems, including social marginalization, family problems, work or school problems, and precipitating crisis events. Ultimately, patterns among all four types of offenders can assist those developing security policy, conducting threat assessments, and attempting to intervene in the lives of at-risk individuals.